The Intensity of Visiting the School Library as an Indicator of Students' Reading Interest in Elementary Schools - Azhari, Ayu; Ramadan, Zaka Hadikusuma (International Journal of Elementary Education, 2022)
The problems that have occurred so far are that schools have not utilized the library as the main means of the education process at school. The teacher has not encouraged students to visit the library intensely, and the students' reading interest is low. This study aims to analyze the intensity of visits, the purpose of students visiting the school library, and the services of the school librarian to students in elementary schools. This type of research is descriptive research with a qualitative approach. The method of collecting data is through interviews, observations, and documentation with instruments in the form of interview guidelines and observation guidelines. Data analysis was done by data reduction, display, and conclusion drawing. The results showed that the intensity of student visits to the school library was 2 to 4 times a week. It was routine and quite good. The purpose of students visiting the school library is known not only to read books but also to discuss and spend time resting. The library services provided by the officers showed that the officers provided information on how to borrow books and reaffirmed the rules while at the library. Besides that, the officers provided services according to service hours. Officers always answer student questions and are fast and precise in providing services.